SYNTHESIS AND CHARACTERIZATION OF SURFACTANT INTERNAL OLEFIN SULFONATE USING MAOS (MICROWAVE ASSISTED ORGANIC SYNTHESIS) METHOD FOR ALKALINE-SURFACTANT INJECTION IN FIELD X, INDONESIA - Hanif Kusuma, Naufal
The alkali-surfactant injection is a commonly used method in the petroleum sector, especially in reservoirs. It is known that each oil reservoir has varying characteristics so a surfactant that matches the conditions of the intended reservoir is needed. In this research, the surfactant synthesized is an anionic Internal Olefin Sulfonate (IOS) surfactant, which will be applied to the X field. The synthesized IOS compound has been designed to fit the X field profile. IOS was synthesized through two stages: internal diolefin synthesis via Wittig reaction and sulfonation of internal diolefin. The precursors used in the Wittig reaction were 1-bromodecane, tryphenylphosphine, glyoxal, and sodium hydrid. In contrast, the precursors used in the internal diolefin sulfonation reaction were internal diolefin, sodium bisulfite, and sodium hypochlorite. The synthesis of IOS was carried out using the Microwave Assisted Organic Chemistry (MAOS) method to increase the efficiency of the reaction time and the yield percentage. The Wittig reaction was carried out at 45 °C and 300 Watts of power for 4 hours, while the internal diolefin sulfonation reaction wascarried out at 75 °C and 300 Wattsof powerfor 3 hours. The Wittig reaction product (Internal diolefin) was confirmed through Thin Layer Chromatography (TLC) analysis and Fourier Transform Infrared (FTIR) spectrum. On TLC analysis using 100% n-hexane eluent, the internal diolefin was confirmed to have a different Retention factor (Rf) valuewiththe used precursor. Basedonthe FTIRspectrum, the internal diolefin was confirmed to be formed through 1636 cm-1 C=C stretching alkene, 2921 cm-1 C-H stretching alkane, and 3070 cm-1 stretching alkene peaks. Furthermore, IOS was confirmed to be formed through TLC analysis, FTIR spectrum, and Nuclear Magnetic Resonance (NMR) spectrum. On TLC analysis using 70% ethyl acetate and 30% methanol eluent systems, IOS was confirmed to have different Rf values with the reaction precursors used. Based on the FTIR spectrum, IOS was confirmed to be formed through the presence of peaks of 978 cm-1 S=O stretching sulfonate, 1636 cm-1 C=C stretching alkene, 2921 cm-1 C-H stretching alkane, and 3070 cm-1 C-H stretching alkene. Based on the NMR spectrum, IOS was confirmed to be formed via ?H 0.81 ppm (t, 6H) and ?C 14.09 ppm indicating the presence of terminal methyl, ?H 3.02 ppm (qt, 1H) and ?C 64.57 ppm indicating a C-S bond, and ?H 3.62 ppm (dt, J1 = 6.4 Hz, J2 = 6.2 Hz, 2H) and ?C 130.69 ppm indicating a C=C bond. Furthermore, the performance test of IOS surfactant as aninjectant in thealkaline-surfactant injection methodwascarried outwith Field Xoil samples. Theperformance tests conducted were the compatibility, phase behaviour, and interfacial tension tests. Based on the compatibility test, the IOS-alkali solution had stable solubility in the reservoir brine for 24 hours. The IOS-alkali solution successfully produced a Winsor type III microemulsion in the phase behaviour test. Moreover, the IOS-alkali solution successfully produced interfacial tension values up to 1.810 x 10-4 mN/m for the interfacial tension test